Buddha vacana paricaya ("Buddhavacana madhu"vina pravēśampuṭa) mattu Milinda praśne - Rajaratnam, G. P., 1909- (SAMP early 20th-century Indian books project, 1937)
Translation of selection from Pali cononical literature, and of Milindapañhā, teratise on basic tenets of Buddhism, written in the form of a dialog between Nāgasena and Menander, Indo-Greek king, 2nd century B.C.